Anticipating Precarity and Risk in Social Innovation Design for Entrenched Place-Based Disadvantage. (2nd January 2019) - Clarke, Rachel; Burkett, Ingrid
Abstract: We outline considerations for anticipating precarity and risk in design for social innovation through a case study tackling place-based disadvantage for young people with The Australian Centre for Social Innovation (TACSI). In shifting the focus from creative or managed risk within the design process, we ask: what practices of decision-making can lay alternative foundations for change for those who are experiencing precarious lives? We contribute an alternative conceptual framing of risk by drawing from Judith Butler's position on precarity as a heightened attentiveness to complex interconnected concerns. In moving towards transformational design, we argue for practices that work through precarity to offer more nuanced understandings of risk when seeking to develop sustainable change. From the perspective of a design team in the midst of a project, we reflect on the value of responding to risk in relation to precarity, highlighting intersectional concerns that support ongoing decision-making. With direct measures of what is considered successful and valuable from design interventions, what becomes most precarious is the lack of recognition of complex personhood, translation through design, and opportunities for working across multiple sites of experimental intervention.